.44 - DeRosso, H.A (Bath : Chivers Press, 2001)
Dan Harland was a legend. A hired gun, Harland had earned a reputation as one of the fastest gunslingers in the West. He didn't like to kill, but he did it with deadly accuracy. The money wasn't too bad, either. However, when he is hired to kill a man who is seemingly all too ready to die, Harland begins to have second thoughts about his occupation and seeks out the shadowy figure who hired him.